Community Radio in South Asia: Reclaiming the Airwaves, Kanchan K. Malik and Vinod Pavarala (eds) (2020). (1st October 2021) - Sahai, Shrinkhla
Review of: Community Radio in South Asia: Reclaiming the Airwaves, Kanchan K. Malik and Vinod Pavarala (eds) (2020)New York: Routledge, 294 pp., ISBN 978-1-138-55853-3, h/bk, 65.42, e-book, 48.95